2004
DOI: 10.1088/0031-9155/49/14/011
|View full text |Cite
|
Sign up to set email alerts
|

Dose perturbation effects in prostate seed implant brachytherapy with I-125

Abstract: EGSnrc Monte Carlo simulation was used to investigate dose perturbation effects in prostate seed implant brachytherapy using 125I radioactive seeds used in implant brachytherapy. Dose perturbation effects resulting from the seed mutual attenuation in a prostate seed implant consisting of 27 seeds were investigated. The results showed that for 125I seeds implanted into the prostate at 1.00 cm, 0.75 cm and 0.50 cm apart (uniform spacing), the dose perturbation effects are up to 10%. The volume of the target occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
1
25
0
1
Order By: Relevance
“…This inter-seed attenuation (ISA) effect depends on radionuclide ( i.e ., photon energy), source encapsulation, seed spacing, or equivalently seed density, which in turn depends on prostate size and seed air-kerma strength. Initial studies using MC simulations of a number of seeds with different spacing [21] or idealized implants [22] reported an effect on conformity and homogeneity indices that becomes negligible for 125 I seeds spaced >0.5 cm apart. Subsequent studies of the ISA effect were performed using MC simulations in clinical, CT-based, pre- or post-implant geometries with results reported in CTV and OAR DVH parameters employed for treatment plan evaluation [23–26].…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…This inter-seed attenuation (ISA) effect depends on radionuclide ( i.e ., photon energy), source encapsulation, seed spacing, or equivalently seed density, which in turn depends on prostate size and seed air-kerma strength. Initial studies using MC simulations of a number of seeds with different spacing [21] or idealized implants [22] reported an effect on conformity and homogeneity indices that becomes negligible for 125 I seeds spaced >0.5 cm apart. Subsequent studies of the ISA effect were performed using MC simulations in clinical, CT-based, pre- or post-implant geometries with results reported in CTV and OAR DVH parameters employed for treatment plan evaluation [23–26].…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…The TG-43u1 calculations overestimate the D 90 values calculated with MCP by 5.8%-12.8%, depending on the seed density and prostate size. This difference corresponds to [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Gy. This is illustrating the systematic effect when taking into account the interseed attenuation and prostate composition corrections in the dosimetry.…”
Section: Overall Comparisonmentioning
confidence: 99%
“…Similar works have been recently published about dosimetric perturbation effects calculated using Monte Carlo methods. Mobit and Badragan 17 have studied the interseed attenuation in a water cube with 27 uniformly distributed seeds. Chibani et al 18 have evaluated the interseed attenuation for idealized and clinical prostate implants.…”
Section: Introductionmentioning
confidence: 99%
“…That study reported a reduction of 6% of the peripheral dose due to the mutual attenuation by neighboring seeds. Mobit et al 34 studied the interseed effect for an array of 27 125 I seeds in a 20 ϫ 20ϫ 20 cm 3 cube of water deposited at 1, 0.75, and 0.5 cm apart. They reported no significant change in dose volume histograms due to the interseed effect provided that the seeds are separated by more than 0.5 cm.…”
Section: Discussionmentioning
confidence: 99%